Analysis of Capital Structure and Profitability on Firm Value of Companies Listed on the Sharia Stock List - Sa’adah, Ulfa Ni’matus; Indana, Rifaatul (Journal of Accounting Inquiry, 2023)
Purpose: This study aims to analyse the capital structure and profitability on the firm value on the Sharia Stock List. Methodology: This study uses independent variables of capital structure, namely Debt to Equity Ratio (DER) and profitability (ROE). The dependent variable is firm value as measured by Tobin's Q variable. The research method is descriptive quantitative research using hypothesis testing. Findings: The results of this study are the capital structure variable partially has a negative and significant effect on firm value. Profitability variable partially has a negative and significant effect on firm value. Novelty: Researcher try to identify and further examine the effect of capital structure and profitability on the value of Sharia Stock List.